1991
DOI: 10.1093/oxfordjournals.jbchem.a123666
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Occurrence and Expression of the Isoforms of Nonspecific Lipid Transfer Protein in Castor Bean Seedlings, and Molecular Cloning of a Full-Length cDNA for a Cotyledon-Specific Isoform1

Abstract: Four kinds of nonspecific lipid transfer proteins (nsLTP) were purified from different organs of castor bean (Ricinus communis L.) seedlings. Amino acid compositions and amino-terminal sequences of the four nsLTPs were determined and compared with those of castor bean isoforms, nsLTP-A, -B, and -C, previously reported [Takishima et al. (1986) Biochim. Biophys. Acta 870, 248-255; Takishima et al. (1988) Eur. J. Biochem. 177, 241-249]. Two isoforms from the cotyledons were identified as nsLTP-A and -C, one isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In contrast, it is consistent with the observations of Douady et al [ 101 and Kader et al [ l l ] who found that after carboxymethyl-Sepharose chromatography, the lipid-transfer activity from maize seeds and spinach-leaf extracts were detected in two and three groups of fractions, respectively. The existence of LTP isoforms has recently been confirmed by Arondel et al 1291 who described the presence of multiple LTP-encoding mRNA and by Tsuboi et al [25] who purified four organ-specific isoforms of LTP from castor-bean seedlings.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, it is consistent with the observations of Douady et al [ 101 and Kader et al [ l l ] who found that after carboxymethyl-Sepharose chromatography, the lipid-transfer activity from maize seeds and spinach-leaf extracts were detected in two and three groups of fractions, respectively. The existence of LTP isoforms has recently been confirmed by Arondel et al 1291 who described the presence of multiple LTP-encoding mRNA and by Tsuboi et al [25] who purified four organ-specific isoforms of LTP from castor-bean seedlings.…”
Section: Discussionmentioning
confidence: 84%
“…LTP from maize, castor bean, spinach, tobacco, and carrot are, as barley LTP, synthesized as preproteins (MUNDY and ROGERS 1986;TCHANG et al 1988;BERNHARD, et al 1991;STERK et al 1991;TSUBOI et al 1991;FLEMING et al 1992;WEIG and KOMOR 1992). Barley LTP is co-translationally transferred across the membrane of the endoplasmic reticulum concomitant with signal peptide cleavage, and signal peptide cleavage can also occur post-translationally (MADRID 1991 b).…”
Section: Discussionmentioning
confidence: 99%
“…A fourth EST with significant but lower homology to LTPl may represent the product of a third gene in Arabidopsis. LTP isoforms have also been found in castor bean (Tsuboi et al, 1991), barley (Mundy and Rogers, 1986;Linnestad et al, 1991), tobacco (Koltunow et al, 1990;Fleming et al, 1992), and wheat (Dieryck et al, 1992), and Southern analysis suggests the presence of severa1 LTP genes in maize (Tchang et al, 1989) and tomato (Torres-Schumann et al, 1992).…”
Section: Discussionmentioning
confidence: 99%